Impacts of Wild Animals on Community People in Dallagaon, Bardiya Nepal - Gupta, Umesh Kumar; Verma, Sant Kumar (Chhahari छहारी, 2026)
This study examines the impact of wild animals on the livelihoods of people living in and around Dallagaon, Bardiya National Park, Nepal. Using interviews, observations, and survey questionnaires, the research explores awareness, safety, economic, psychological, and social effects of wildlife. Findings (mean score 4.3) reveal frequent crop and property damage, financial losses, and widespread fear and stress disrupting daily life. Despite tourism benefits, economic and emotional hardships prevail. A mean score 2.75 indicates community dissatisfaction with government support and compensation. Nevertheless, local awareness and collective efforts show resilience. The study concludes that human–wildlife conflict is a multidimensional issue requiring integrated solutions, improved preventive measures, fair compensation, and community-centered policies for sustainable coexistence.